Analysis of fractal dimension and radiomorphometric indices of mandible on panoramic radiographs in end-stage renal disease at a tertiary care centre in South India - Anju Redhu; B Suman (Wolters Kluwer Medknow Publications, 2021)
Background and Objectives: Chronic kidney disease (CKD), especially, end-stage renal disease (ESRD), is associated with endocrinal and metabolic alterations that negatively affect the skeletal system, and can result in renal osteodystrophy (ROD) and secondary osteoporosis. These changes can affect the mandibular density and thus can be reflected in mandible on panoramic radiographs (PR), which are frequently assessed by oral physicians. This study attempted to evaluate these mandibular skeletal alterations using radiomorphometric indices (RI) and fractal dimension (FD) analysis, in patients with ESRD, thereby aiding in their appropriate management for the dental treatment. Material and Methods: Retrospective data (including digital PRs) of 30 patients with CKD (ESRD) who were above 18 years of age were retrieved and 30 age and sex-matched healthy individuals having met the selection criteria were selected. Digital PR were used to assess the mandibular cortical index (MCI), mental index (MI), panoramic mandibular index (PMI), and FD by using ImageJ program. Results: No statistically significant difference was noted among the study groups and controls for the mean values of PMI, FD, and distribution of MCI category (P > 0.05). However, the mean value of MI was significantly reduced among the kidney patients as compared to the controls (P < 0.05). No significant correlation was noted between duration of diseases, RI (MCI, MI, PMI) and FD. Conclusion: MI values of patients with ESRD were found to be lower than those in control subjects. This finding suggests that MI analysis might be a promising, simple, and cost-effective tool for evaluating cortical bone structure in this high-risk population and any signs of osteoporosis could be withheld at the earliest stage with a prompt referral.